Strategic psycholinguistics and linguodidactics: contribution of the department of theory and methods of teaching Russian as a foreign language in the development of new scientific directions - Lebedinskiy, Sergey I. (Journal of the Belarusian State University. Philology, 2024)
The article is dedicated to the 80th anniversary of the faculty of philology of the Belarusian State University. A brief overview of scientific work carried out by employees of the department of theory and methods of teaching Russian as a foreign language in line with two new scientific directions – strategic psycholinguistics and strategic linguodidactics is given. It is emphasised that the incentives for the creation of these directions were the absence in modern linguodidactics of a scientifically based theory of the acquisition of languages, including Russian as a foreign language, and the attempt to build it within the framework of a strategic paradigm. It is shown that the publications of scientists of the department confirm the scientific foundation of the strategic theory of mastering Russian as a foreign language, analyse the typology of strategies for mastering the Russian language by foreigners and demonstrate their variability, experimentally study the cognitive styles of information processing by foreigners when mastering the Russian language, and characterise some strategies for teaching Russian as a foreign language at the level of aspects of language and types of speech activity. It has been proven that a strategic approach to the acquisition of a foreign language and mastery of foreign language speech makes it possible to describe the processes of language acquisition and speech acquisition in a single coordinate system, within the framework of which it is planned to develop the theory of step-by-step acquisition of foreign languages. In the course of the conducted research, it was established that with a strategic approach to the analysis of speech processes, the uniqueness, variability, multi-vector and multi-level formation of linguistic and communicative competence can be reduced to a relatively small list of general (universal) and individual strategies that foreign speakers use when mastering Russian language. It was found that what is common in the strategies for acquiring a foreign language and mastering foreign language speech is the principle of implementing speech-mental operations, and individual methods of achieving the goal are distinguished by uniqueness and variability and largely depend on the intellectual and cognitive-style abilities of the students.
Keywords: strategic psycholinguistics; strategic linguodidactics; strategic theory of language and speech acquisition; language acquisition strategies; language use strategies; learning strategies; strategies for producing; reproducing and understanding speech